1999
DOI: 10.1246/cl.1999.1327
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Decomposition of Pure Water over NiO Supported on KTa(M)O3 (M = Ti4+, Hf4+, Zr4+) Perovskite Oxide

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…We also wish to point out, that the strong vertical displacement of the Ni3 layer away from Ni4 towards the O2 layer (for Ni-termination, and similar for O-termination), is not observed in the experimental relaxations found by Barbier et al [14] (vertical splitting Ni3/Ni4: d 2S À d 2 0X078 # A in Ref. [5] vs. 0.88 # A in this work). As will be argued below, we consider the merging of Ni3 and O2 layers an important aspect of structural stability.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…We also wish to point out, that the strong vertical displacement of the Ni3 layer away from Ni4 towards the O2 layer (for Ni-termination, and similar for O-termination), is not observed in the experimental relaxations found by Barbier et al [14] (vertical splitting Ni3/Ni4: d 2S À d 2 0X078 # A in Ref. [5] vs. 0.88 # A in this work). As will be argued below, we consider the merging of Ni3 and O2 layers an important aspect of structural stability.…”
Section: Discussionmentioning
confidence: 47%
“…The NiO(1 1 1) surface is known to exhibit important physical and chemical properties ± NiO is antiferromagnetic at low temperature [3] and a catalytic compound [4,5]. The alternating layers of Ni 2 and O 2À ions produce a non-vanishing dipole moment perpendicular to the surface, resulting in Surface Science 470 (2000) 1±14 www.elsevier.nl/locate/susc an unstable bulk terminated NiO(1 1 1) polar surface with a nominally in®nite surface energy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemical (PEC) water splitting is one of the promising procedures to generate hydrogen as a zero‐emission energy carrier alternative to polluting fossil fuels. [ 11–20 ] During the PEC water splitting, solar energy can facilitate the occurrence of the hydrogen production half‐reactions at an electrode coated by specialized semiconductors or PEC materials. [ 21–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zou et al have found that Ni‐doped InTaO 4 can decompose H 2 O upon activation with visible light,6 as can the mixed SrTiO 3 /WO 3 compound reported by Sayama et al7, 8 In a previous study we found that Zr‐doped KTaO 3 exhibits a high activity, splitting H 2 O into almost stoichiometric amounts of H 2 and O 2 9. 10 However, these photocatalysts mainly consist of oxide semiconductors combined with a metal or metal oxide such as Pt or NiO. On the other hand, dye‐sensitized solar cells are attracting a great deal of interest because of their simple structure and high efficiency 11.…”
Section: Photocatalytic Splitting Of Water Into H2 and O2 By K095ta0mentioning
confidence: 62%